2018
DOI: 10.1016/j.scitotenv.2018.06.101
|View full text |Cite
|
Sign up to set email alerts
|

A review on sediment bioflocculation: Dynamics, influencing factors and modeling

Abstract: Sediment in a water column provides excellent substratum for microorganism colonization, and biological processes would alter the physical and chemical of sediment, resulting in substantial changes in sediment dynamics. The flocculation of sediment with biological processes are defined as sediment bioflocculation, which has been ubiquitously observed across aquatic ecosystems, activated sludge plants and bioflocculant applications, as a result of various processes involving particle aggregation and breakage un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 182 publications
0
46
0
Order By: Relevance
“…Flocs in natural waters constitute a complex matrix of microbial communities, organic and inorganic particles 38 . Thus, while SPM concentration and local turbulence are prime determinants of floc size 39,40 , also the organic matter and the microbial organisms that are associated with the flocs determine their aggregation and disaggregation rate, their strength and shape 22,41–43 . Particularly in the Scheldt, the decreasing OM and nutrient inputs, decreasing ammonium concentrations and increasing oxygenation, have been accompanied by a change in the balance between bacterial heterotrophic and chemo-autrophic metabolism (i.c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flocs in natural waters constitute a complex matrix of microbial communities, organic and inorganic particles 38 . Thus, while SPM concentration and local turbulence are prime determinants of floc size 39,40 , also the organic matter and the microbial organisms that are associated with the flocs determine their aggregation and disaggregation rate, their strength and shape 22,41–43 . Particularly in the Scheldt, the decreasing OM and nutrient inputs, decreasing ammonium concentrations and increasing oxygenation, have been accompanied by a change in the balance between bacterial heterotrophic and chemo-autrophic metabolism (i.c.…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical determinants of aggregation-disaggregation dynamics of cohesive sediments is currently a hot research topic (e.g. 22 ). In estuaries this is particularly important since the settling velocity of aggregates co-determines the location and intensity of the maximum turbidity zone.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix of the biofilm microenvironment is comprised mostly of extracellular polymeric substances (EPS) (Flemming, Neu, & Wozniak, 2007;Wingender, Neu, & Flemming, 1999), which are synthesized by the biofilm microbial community. The properties of these EPS are influential on the sediments upon which they establish, altering their physicochemical characteristics and, therefore, their dynamics through bioflocculation (Lai, Fang, Huang, He, & Reible, 2018). An experimental study (Valentine, Mariotti, & Fagherazzi, 2014) found that the erodibility and resulting resuspension of settled cohesive sediments was reduced with weak biofilm EPS growth when exposed to low shear stress (<0.1 Pa).…”
Section: Biotic Controls On Fine Sediment Transport and Storagementioning
confidence: 99%
“…A recent advance in physical-chemical-biological interactions is the recognition that EPSs, and other cohesive fine-grained material, are major controls on sedimentary processes. Cohesive sediments and sticky substances, including EPS, impact the erodibility of substrate, and sediment transport and deposition processes (e.g., Malarkey et al, 2015;Lai et al, 2018;Lichtman et al, 2018). An associated advance is the understanding that many sedimentary processes involve mixed grain-size and grain-type flows (polydisperse), and challenge established bedform-phase diagrams that assume very narrow (monodisperse) grain-size distributions, leading to reanalysis of many sedimentary structures, and process interpretations (Baas et al, 2016).…”
Section: Life and Sediment Interactionsmentioning
confidence: 99%